Moisture curable polyurethane hot melt adhesive composition
By developing a wet curable polyurethane hot melt adhesive composition containing polyurethane prepolymer, the lack of initial bond strength and fluidity of fluidic sealants in the prior art is solved, and the effect of efficient filling of voids and providing high bond strength in electronic devices is achieved.
Patent Information
- Application Number
- CN202280100036.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the fluid sealant used for void filling in electronic devices lacks high initial bonding strength, resulting in delays in production, and the filler is prone to clogging the needle, affecting fluidity.
A wet curable polyurethane hot melt adhesive composition is developed, which comprises at least one polyurethane prepolymer obtained by reacting a polyol mixture with a polyisocyanate having isocyanate groups. The composition is solid at room temperature, can melt into a viscous liquid at medium temperature, and forms a high-strength crosslinking structure after cooling and curing.
The adhesive composition exhibits excellent fluidity on various substrates, can effectively fill gaps, and has good bonding strength after curing, avoiding adverse effects on other properties.
Smart Images

Figure BDA0005310206240000151 
Figure BDA0005310206240000161 
Figure BDA0005310206240000162
Abstract
Description
Technical Field
[0001] The present invention relates to a moisture-curable polyurethane hot-melt adhesive composition, in particular, to a moisture-curable polyurethane hot-melt adhesive composition exhibiting excellent fluidity and bonding strength when cured, a preparation method thereof and use thereof. Background Art
[0002] In the electronics field, the use of silicone formulations or two-component polyurethane adhesives to fill gaps between substrates is generally known in the art as “fluid sealants.” However, these fluid sealants do not provide high initial bond strengths, which leads to considerable delays in production.
[0003] The polyurethane hot-melt adhesive composition of moisture curable is solid at room temperature, melts into viscous liquid when being heated to medium temperature, and is applied to substrate to be bonded.Then, the adhesive composition of this melting is cooled and solidified to form the initial bonding with this substrate, and it can further react with moisture to form cross-linked structure and realize high ultimate strength.The polyurethane hot-melt adhesive composition of moisture curable is environmentally friendly, fast-curing and has high adhesiveness, is therefore suitable for bonding various substrate materials, for example polycarbonate (PC), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polymethyl methacrylate (PMMA), metal and inorganic glass in electronic device.Yet, the polyurethane hot-melt adhesive composition of moisture curable that is used for gap filling in electronic device requires that this adhesive has excellent fluidity, and does not detract from other properties in aspects such as adhesiveness, curing time and impact resistance.
[0004] Most of the prior art focuses on improving the technology of dispensing equipment to solve this problem. In this regard, few have specifically developed adhesive compositions. For example, CN 101418203A discloses that chain extenders and fillers can greatly improve the viscosity of adhesives. However, the filler tends to clog the needle, which affects the fluidity of adhesive dispensing.
[0005] Therefore, there remains a need to develop moisture-curable polyurethane hot melt adhesive compositions that exhibit excellent flow properties on substrates to achieve gap filling purposes without adversely affecting other important properties such as bond strength. Summary of the invention
[0006] After intensive studies, the present inventors have found that the above problems can be solved by a moisture-curable polyurethane hot melt adhesive composition comprising at least one polyurethane prepolymer obtained by reacting a component comprising (A) a polyol mixture with (B) at least one polyisocyanate having at least two isocyanate groups in one molecule. The (A) polyol mixture comprises:
[0007] (a) at least one polyol which is liquid at room temperature,
[0008] (b) at least one crystalline polyester polyol having a melting point below 70°C, and
[0009] (c) 0 to less than 15.4 wt% of at least one crystalline polyester polyol having a melting point of not less than 70°C, based on the total amount of the composition.
[0010] In another aspect of the present invention, a method for preparing the moisture-curable polyurethane hot melt adhesive composition of the present invention is provided.
[0011] In another aspect of the present invention, a laminate is provided, which includes a first substrate, a second substrate, and an adhesive layer sandwiched between them, wherein the first substrate and the second substrate are independently selected from glass, resin, metal and polyolefin, and the adhesive layer is formed by curing the adhesive composition of the present invention.
[0012] In yet another aspect of the present invention, an electronic device is provided, which includes the article of the present invention.
[0013] In another aspect of the present invention, there is provided use of the adhesive composition and laminate of the present invention in a touch screen, a mobile phone, a liquid crystal display, a polymer panel, a film, a conductive layer, a protective layer or an ink layer.
[0014] The present invention features moisture-curable polyurethane hot melt adhesive compositions that have excellent flow properties on a variety of substrates and good bond strength when cured. DETAILED DESCRIPTION
[0015] It will be appreciated by those skilled in the art that the present invention is merely a description of an exemplary embodiment and is not intended to limit the broader aspects of the present invention. Unless clearly indicated otherwise, each aspect so described may be combined with any one or more other aspects. In particular, any feature indicated as being preferred or advantageous may be combined with any one or more other features indicated as being preferred or advantageous.
[0016] Unless otherwise stated, in the context of the present invention, the terms used should be interpreted according to the following definitions.
[0017] As used herein, the terms "a," "an," and "the" include both singular and plural referents unless otherwise specified.
[0018] As used herein, the term "comprising" is synonymous with "including," or "containing," and is inclusive or open-ended and does not exclude additional, unrecited members, elements, or processing steps.
[0019] Unless otherwise stated, the recitation of numerical endpoints includes all numbers and fractions subsumed within the corresponding range, as well as the recited endpoint.
[0020] Unless stated otherwise, molecular weights refer to number-average molecular weight (Mn). Unless stated otherwise, all molecular weight data refer to the values obtained by gel permeation chromatography (GPC), for example according to DIN 55672.
[0021] All references cited in this specification are herein incorporated by reference in their entirety.
[0022] Unless otherwise defined, all terms used in the present invention, including technical and scientific terms, have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0023] The present invention relates to a moisture-curable polyurethane hot melt adhesive composition comprising at least one polyurethane prepolymer obtained by reacting a component comprising (A) a polyol mixture with (B) at least one polyisocyanate having at least two isocyanate groups in one molecule. The (A) polyol mixture comprises:
[0024] (a) at least one polyol which is liquid at room temperature,
[0025] (b) at least one crystalline polyester polyol having a melting point below 70°C, and
[0026] (c) 0 to less than 15.4 wt% of at least one crystalline polyester polyol having a melting point of not less than 70°C, based on the total amount of the composition.
[0027] Polyurethane prepolymer
[0028] The moisture-curable polyurethane hot melt adhesive composition comprises at least one polyurethane prepolymer obtained by reacting a component comprising a polyol mixture with at least one polyisocyanate having at least two isocyanate groups in one molecule.
[0029] In one embodiment, the amount of the isocyanate functional polyurethane prepolymer in the present invention is 60 to 99.9 wt %, preferably 65 to 95 wt %, based on the total weight of the adhesive composition.
[0030] In some embodiments, the polyurethane prepolymers of the present invention have an NCO content of 1.3 wt% to 6 wt%.
[0031] In other embodiments, the polyurethane prepolymer has a number average molecular weight of 5,000 to 30,000 g / mole, preferably 8,000 to 15,000 g / mole, and more preferably 8,500 to 10,000 g / mole.
[0032] (A) Polyol mixture
[0033] According to the present invention, the polyol mixture (A) comprises: (a) at least one polyol that is liquid at room temperature; (b) at least one crystalline polyester polyol having a melting point below 70°C; and (c) 0 to less than 15.4 wt% of at least one crystalline polyester polyol having a melting point not less than 70°C, based on the total amount of the composition.
[0034] (a) Liquid polyols
[0035] According to the present invention, the polyol mixture used in the present invention comprises at least one polyol that is liquid at room temperature. The liquid polyol can provide flow properties to the adhesive composition.
[0036] Therefore, the liquid polyol has a glass transition temperature (Tg) of not higher than 0° C., preferably -100° C. to 0° C., more preferably -50° C. to 0° C. If the Tg of the liquid polyol is too high, it is more difficult to be in a liquid state.
[0037] In some embodiments, the at least one polyol that is liquid at room temperature may be selected from liquid polyester polyols and / or liquid polyether polyols.
[0038] Examples of liquid polyester polyols can be obtained by the ring-opening polymerization of lactones such as ε-caprolactone, and / or can be derived from dibasic alcohols and dibasic acids. Examples of dibasic alcohols available in the preparation of preferred polyester polyols include ethylene glycol, diethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and mixtures thereof. Examples of dibasic acids available in the preparation of preferred polyester polyols include succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and 1,12-dodecane dioic acid, dimer acid, and mixtures thereof. Included within the scope of available dibasic acids are various dibasic acid derivatives, such as carboxylic acid esters (particularly methyl esters and ethyl esters), acyl halides (such as acyl chlorides) and anhydrides, and mixtures thereof.
[0039] Specific examples of suitable liquid polyester polyols include poly(hexamethylene adipate) polyols, poly(butylene adipate) polyols, poly-ε-caprolactone polyols, poly(hexamethylene dodecanedioate) polyols, poly(hexamethylene adipate terephthalate) polyols, and mixtures thereof.
[0040] Alternatively, liquid polyether glycol can be used in the present invention.Compared to liquid polyester polyol, using liquid polyether glycol in the composition can increase the bond strength of the adhesive composition when solidified.These liquid polyether glycols can be obtained by copolymerizing at least one compound in ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran (THF) etc. with at least one compound having an average of at least two active hydrogen atoms in a molecule, for example, the polyol listed above, the polyol comprises ethylene glycol, propylene glycol, dipropylene glycol, glycerine and their mixture.Other suitable polyols comprise sucrose, ethylenediamine, propylene diamine, triethanolamine, 1,2-propanedithiol and their mixture.
[0041] Preferred liquid polyether polyols may be polypropylene glycol, polytetramethylene ether glycol, poly(oxypropylene) glycol, polyethylene oxide, polybutylene oxide, and ethylene oxide-terminated forms of any of the foregoing. The most preferred polyether polyols are polytetramethylene ether glycol, poly(oxypropylene) glycol, and ethylene oxide-terminated poly(oxypropylene) glycol.
[0042] In a preferred embodiment, the liquid polyol has a number average molecular weight of 400 to 8,000 g / mole, preferably 500 to 5,000 g / mole, more preferably 1,000 to 4,000 g / mole.
[0043] The liquid that is a polyol at room temperature may be used alone, or a combination of at least two different liquid polyols may be used.
[0044] Commercially available products may be used in the present invention. Suitable commercially available liquid polyether polyols include Voranol TM 2104, 2110, 2120, 2140. And suitable commercially available liquid polyester polyols are sold under the trade name of the DYNACOLL 7200 series from Evonik Industries AG (Germany), including DYNACOLL 7210, 7230, 7231, 7250, 7255, and the like.
[0045] Particularly preferably, the component (a) may be added in an amount of greater than 0 wt% to 60 wt%, preferably 10 wt% to 60 wt%, more preferably 15 wt% to 50 wt%, based on the total weight of the composition.
[0046] (b) Crystalline polyester polyol having a melting point below 70°C
[0047] According to the present invention, the polyol mixture used in the present invention comprises at least one crystalline polyester polyol (b) having a melting point below 70°C.
[0048] The term "melting point" as used herein is determined by a melting curve obtained by the differential scanning calorimetry (DSC) method.
[0049] In a preferred embodiment, component (b) comprises at least one crystalline polyester polyol having a melting point below 60° C., more preferably 40° C. to 55° C. In a particularly preferred embodiment, the component (b) comprises at least two crystalline polyester polyols having different melting points within the above range.
[0050] In a preferred embodiment, component (b) has a number average molecular weight of 1,000 to 20,000 g / mole, preferably 2,000 to 15,000 g / mole, more preferably 2,000 to 8,000 g / mole.
[0051] Examples of such crystalline polyester polyols with a melting point below 70°C can be obtained by ring-opening polymerization of lactones such as ε-caprolactone, and / or can be derived from diols and dibasic acids. Examples of diols available in the preparation of preferred polyester polyols include ethylene glycol, diethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and mixtures thereof. Examples of dibasic acids available in the preparation of preferred polyester polyols include succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and 1,12-dodecane dioic acid, dimer acid, and mixtures thereof. Included within the scope of available dibasic acids are various dibasic acid derivatives, such as carboxylates (particularly methyl and ethyl esters), acyl halides (such as acyl chlorides) and anhydrides, and mixtures thereof.
[0052] In a preferred embodiment, component (b) comprises at least one crystalline polycaprolactone polyol having a melting point below 70°C. The polycaprolactone polyol is a polyester polyol prepared by ring-opening polymerization of ε-caprolactone with a polyol initiator or a polyamine initiator. Useful polyol initiators include, for example, diols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, bisphenol A, and resorcinol; triols such as glycerol, 1,2,6-hexanetriol, and 1,1,1-tri(hydroxymethyl)propane; tetraols such as pentaerythritol, erythritol, and methyl glucoside; hexaols such as sorbitol and dipentaerythritol; and octanols such as sucrose. The polyamine initiators that can be used include, for example, diamines such as ethylenediamine, propylenediamine, hexamethylenediamine, and hydrazine; and at least trifunctional polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentylamine. These initiators can be used alone or in combination of two or more of these initiators, preferably diols and diamines.
[0053] Specific examples of suitable crystalline polyester polyols having a melting point below 70°C include poly(hexamethylene adipate) polyols, poly(butylene adipate) polyols, poly-ε-caprolactone polyols, poly(hexamethylene dodecanedioate) polyols, poly(hexamethylene adipate terephthalate) polyols, polycaprolactone polyols, and mixtures thereof.
[0054] Suitable commercially available crystalline polyester polyols having a melting point below 70°C are sold under the tradenames of the DYNACOLL 7300 series from Evonik Industries AG (Germany), including DYNACOLL 7360, 7361, 7362, 7363, 7365, 7381, etc.; and CAPA TMA series of trade names sold from Ingevity, including CAPA TM 2201, 2205, 2209, 2302, 2304, 2402, etc. Suitable commercially available crystalline polycaprolactone polyols having a melting point below 70°C for use as component (b) are 205, 208, 210, 210CP from Daicel.
[0055] Particularly preferably, the component (b) may be added in an amount of greater than 0 to 80 wt%, preferably 10 to 80 wt%, more preferably 15 to 60 wt%, based on the total weight of the composition (b).
[0056] (c) a crystalline polyester polyol having a melting point of not less than 70°C
[0057] According to the present invention, the polyol mixture used in the present invention comprises 0 to less than 15.4 wt % of at least one crystalline polyester polyol having a melting point of not less than 70° C., based on the total amount of the composition.
[0058] In a preferred embodiment, the polyol mixture does not contain any crystalline polyester polyol (c) having a melting point of not less than 70° C. In other embodiments, the crystalline polyester polyol should be present in an amount of 0 to less than 15.4 wt %, preferably 0 to less than 12 wt %, more preferably 0 to less than 11 wt %, even more preferably 0 to less than 5 wt %, based on the total amount of the composition, otherwise the fluidity of the adhesive composition will be significantly reduced.
[0059] In a preferred embodiment, a crystalline polyester polyol having a melting point of not less than 70° C. to 120° C. is used as component (c) of the present invention.
[0060] Specific examples of suitable crystalline polyester polyols having a melting point of not less than 70° C. include poly(hexanediol dodecanedioic acid) polyol, poly(butylene glycol dodecanedioic acid) polyol, and mixtures thereof.
[0061] Suitable commercially available crystalline polyester polyols having a melting point of not less than 70° C. are DYNACOLL 7380, 7330, 7340 and the like from Evonik Industries AG (Germany).
[0062] (B) Polyisocyanate
[0063] The moisture-curable polyurethane hot melt adhesive composition comprises at least one polyurethane prepolymer obtained by reacting (A) the polyol mixture of the present invention with (B) at least one polyisocyanate having at least two isocyanate groups in one molecule.
[0064] In a preferred embodiment, the ratio of component (A) to component (B) is selected so that the molar ratio of NCO to OH is from 1.3 to 4.0.
[0065] Useful polyisocyanates include any suitable isocyanate having at least two isocyanate groups in one molecule, including, for example, aliphatic isocyanates, cycloaliphatic isocyanates, araliphatic isocyanates, arylalkyl isocyanates and aromatic isocyanates, and mixtures thereof.
[0066] Preferred polyisocyanates may be selected from 4,4-diphenylmethane diisocyanate (MDI), hydrogenated MDI (H12MDI), partially hydrogenated MDI (H6MDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), 4,4-diphenyldimethylmethane diisocyanate, dialkylene diphenylmethane diisocyanate, tetraalkylene diphenylmethane diisocyanate, 4,4-dibenzyl diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isomers of toluene diisocyanate (TDI), 1-methyl-2,4-diisocyanatocyclohexane, 1,6-diisocyanato-2,2,4-trimethylhexane, 1,6-diisocyanato-2,4,4-trimethylhexane, 1-isocyanatomethyl-3-isocyanato-1, 5,5-trimethylcyclohexane (IPDI), tetramethoxybutane-1,4-diisocyanate, naphthalene-1,5-diisocyanate (NDI), butane-1,4-diisocyanate, hexane-1,6-diisocyanate (HDI), dicyclohexylmethane diisocyanate, 2,2,4-trimethylhexane-2,3,3-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, ethylene diisocyanate, methylene triphenyl triisocyanate (MIT), diisocyanatoethyl phthalate, trimethylhexamethylene diisocyanate, 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, and dimer fatty acid diisocyanate, lysine ester diisocyanate, 4,4-dicyclohexylmethane diisocyanate, 1,3-cyclohexane or 1,4-cyclohexane diisocyanate, and mixtures thereof. The most preferred polyisocyanate is 4,4-diphenylmethane diisocyanate (MDI) and its isomers, chain-extended MDI, and mixtures thereof.
[0067] Useful commercially available polyisocyanates include MONDUR from Covestro ISONATE from Dow Chemical Company TM 50OP and ISONATE TM125M and available from Covestro Polymers (China) Co., Ltd. 44C.
[0068] Particularly preferably, component (B) may be added to the adhesive composition in an amount of 5 wt % to 50 wt %, preferably 10 wt % to 35 wt %, preferably 10 wt % to 30 wt %, based on the total weight of the composition.
[0069] Thermoplastic resin
[0070] The adhesive composition according to the present invention further optionally comprises at least one thermoplastic resin to provide the adhesive composition with high strength.
[0071] For purposes of the present invention, thermoplastic resins are distinguished from thermosetting resins, which solidify via crosslinking or curing when subjected to heat and / or to a suitable curing agent. Thermoplastic resins described herein include any non-reactive thermoplastic resin, preferably any non-reactive thermoplastic resin that is substantially free of unreacted and monomeric isocyanates.
[0072] Suitable thermoplastic resins can be selected from polyesters, phenoxy resins, phenolic resins, acrylic polymers, acrylic block copolymers, acrylic polymers with tertiary alkylamide functional groups, polysiloxane polymers, polystyrene copolymers, polyvinyl polymers, divinylbenzene copolymers, polyetheramides, polyvinyl acetals, polyvinyl butyrals, polyvinyl acetols, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, methylene polyvinyl ether, cellulose acetate, styrene-acrylonitrile copolymers, amorphous polyolefins, thermoplastic urethanes, polyacrylonitrile, ethylene vinyl acetate copolymers, ethylene vinyl acetate terpolymers, functionalized ethylene vinyl acetate, ethylene acrylate copolymers, ethylene acrylate terpolymers, ethylene butadiene copolymers and / or block copolymers, styrene butadiene block copolymers, polycaprolactone, and mixtures thereof.
[0073] In a preferred embodiment, the thermoplastic resin has a number average molecular weight of 8,000 to 100,000 g / mol, preferably 8,000 to 80,000 g / mol, more preferably 20,000 to 50,000 g / mol.
[0074] Particularly preferably, the thermoplastic resin is present in the adhesive composition in an amount of 0 wt % to 40 wt %, preferably 5 wt % to 30 wt %, based on the total weight of the composition.
[0075] Other components
[0076] Other additives may be added to the adhesive composition. Such additives may be those commonly used in the art, such as colorants, antioxidants, and the like.
[0077] Examples of colorants include pigments which may be selected from: metal oxide pigments; titanium dioxide, optionally surface-treated titanium dioxide; zirconium oxide or cerium oxide; zinc oxide; iron oxides (black, yellow or red); chromium oxide; and manganese.
[0078] Examples of the antioxidant include phenols such as BHT (butylated hydroxytoluene), octadecyl-3,5-di(1,1-dimethyl)-4-hydroxybenzene-propionate, and pyrogallol; phosphites such as triphenyl phosphite, tris(nonylphenyl) phosphite; or thioesters such as dilauryl thiodipropionate.
[0079] Adhesive composition
[0080] In a preferred embodiment, the present invention provides a moisture-curable polyurethane hot melt adhesive composition, based on the total weight of the composition, comprising:
[0081] greater than 0 to 60 wt%, preferably 10 to 60 wt%, more preferably 15 to 50 wt% of at least one polyol that is liquid at room temperature;
[0082] greater than 0 to 80 wt%, preferably 10 to 80 wt%, more preferably 15 to 60 wt% of at least one crystalline polyester polyol having a melting point below 70°C;
[0083] 0 to less than 15.4 wt %, preferably 0 to less than 12 wt %, more preferably 0 to less than 11 wt %, even more preferably 0 to less than 5 wt % of at least one crystalline polyester polyol having a melting point of not less than 70° C.; and
[0084] 5 to 50 wt %, preferably 10 to 35 wt %, preferably 10 to 30 wt % of at least one polyisocyanate having at least two isocyanate groups in one molecule.
[0085] The method for preparing a moisture-curable polyurethane hot melt adhesive composition comprises the following steps:
[0086] (i) mixing a polyol and, if present, a thermoplastic resin at a temperature of 110 to 160° C., and then applying a vacuum;
[0087] (ii) lowering the reaction temperature and adding a polyisocyanate having at least two isocyanate groups in one molecule at a temperature of 70 to 130° C., and then controlling the temperature at 90 to 130° C.;
[0088] (iii) adding optional additives and mixing until homogeneous; and
[0089] (iv) discharging the mixture, preferably discharging the mixture at a temperature of 90 to 150° C. under nitrogen protection.
[0090] The equipment used for these mixing, stirring, dispersing, etc. is not particularly limited. Automatic mortar, Henschel mixer, three-roll mill, ball mill, planetary mixer, bead mill and the like equipped with agitator and heater can be used. In addition, a suitable combination of these equipments can be used. The preparation method of the curable composition is not particularly limited, as long as a composition in which the above components are uniformly mixed can be obtained.
[0091] The moisture-curable polyurethane hot melt adhesive composition of the present invention may be heat curable, preferably heat curable at a temperature below 100°C, more preferably below 80°C.
[0092] The moisture-curable polyurethane hot melt adhesive composition of the present invention can be readily manufactured using other conventional production techniques.
[0093] Laminate, electronic device and use thereof
[0094] In another aspect of the present invention, a laminate is provided, which includes a first substrate, a second substrate and an adhesive layer sandwiched between them, wherein the first substrate and the second substrate are independently selected from glass, resin, metal and polyolefin, and the adhesive layer is formed by curing the adhesive composition of the present invention.
[0095] The first substrate and / or the second substrate may have a single material and a single layer, or may include multiple layers of the same or different materials. The multiple layers may be continuous or discontinuous.
[0096] The substrates of the articles described herein can have a variety of properties, including rigidity (e.g., a rigid substrate, i.e., the substrate cannot be bent by an individual using two hands, or breaks if an attempt is made to bend the substrate using two hands), flexibility (e.g., a flexible substrate, i.e., the substrate can be bent by using no more than two hands), porosity, conductivity, lack of conductivity, and combinations thereof.
[0097] The substrate of the article can be in various forms, including, for example, fibers, threads, yarns, woven fabrics, nonwovens, films (e.g., polymer films, metallized polymer films, continuous films, discontinuous films, and combinations thereof), foils (e.g., metal foils), sheets (e.g., metal sheets, polymer sheets, continuous sheets, discontinuous sheets, and combinations thereof), and combinations thereof.
[0098] Useful substrate materials for use in the present invention include, for example: polymers (e.g., polycarbonate, ABS resin (acrylonitrile-butadiene-styrene resin); liquid crystal polymers; polyolefins (e.g., polypropylene, polyethylene, low-density polyethylene, linear low-density polyethylene, high-density polyethylene, polypropylene, and oriented polypropylene, copolymers of polyolefins and other comonomers); polyether terephthalate; ethylene-vinyl acetate; ethylene-methacrylic acid ionomer; ethylene-vinyl alcohol copolymers (ethylene-vinyl-alcohols); polyesters, such as polyethylene terephthalate, polycarbonates; polyamides, such as nylon-6 and nylon-6,6; Polyvinyl chloride; polyvinylidene chloride; cellulose products; polystyrene; and epoxy resins); polymer composites (e.g., composites of polymers with metals, cellulose, glass, polymers, and combinations thereof); metals (aluminum, copper, zinc, lead, gold, silver, platinum, and magnesium, and metal alloys such as steel (e.g., stainless steel), tin, brass, and magnesium and aluminum alloys); carbon-fiber composites; other fiber-based composites; graphene; fillers; glass (e.g., alkali-aluminosilicate toughened glass and borosilicate glass); quartz; boron nitride; gallium nitride; sapphire; silicon; carbides; ceramics; and combinations thereof, preferably liquid crystal polymers, glass, and combinations thereof.
[0099] The curable composition can be applied to the substrate using any suitable application method, including, for example, automated fine line dispensing, jet dispensing, slot die coating, roller coating, gravure coating, transfer coating, pattern coating, screen printing, spray coating, filament coating, by extrusion, air knife, trailing blade, brush coating, dip coating, blade coating, offset gravure coating, rotogravure coating, and combinations thereof. The curable composition can be applied as a continuous or discontinuous coating, in a single layer or multiple layers, and combinations thereof.
[0100] Optionally, the surface of the substrate to which the curable adhesive composition is applied is treated to enhance adhesion using any suitable method for enhancing adhesion to the surface of a substrate, including, for example, corona treatment, chemical treatment (e.g., chemical etching), flame treatment, abrasion, and combinations thereof.
[0101] In another aspect of the present invention, an electronic device is provided, which includes the article of the present invention.
[0102] Exemplary electronic devices include computers and computer equipment, such as telecommunications and data communications devices, such as 5G stations, etc.; printers, fax machines, scanners, keyboards, etc.; medical sensors; automotive sensors, etc.; wearable electronic devices (e.g., watches and glasses), handheld electronic devices (e.g., phones (e.g., cellular phones and cellular smartphones), cameras, tablets, e-readers, monitors (e.g., monitors used in hospitals, and monitors used by health care workers, athletes, and individuals), watches, calculators, mice, touchpads, and joysticks), computers (e.g., desktop computers and laptop computers), computer display screens, televisions, media players, household appliances (e.g., refrigerators, washing machines, dryers, ovens, and microwave ovens), light bulbs (e.g., incandescent lamps, light emitting diodes, and fluorescent lamps), and articles including visibly transparent or transparent parts, glass housing structures, protective transparent covers for displays or other optical components.
[0103] Another aspect of the present invention relates to the use of the adhesive composition in a touch screen, a mobile phone, a liquid crystal display, a polymer panel, a film, a conductive layer, a protective layer or an ink layer.
[0104] Example
[0105] The following examples are intended to help those skilled in the art better understand and practice the present invention. The scope of the present invention is not limited by the examples, but is defined in the appended claims. Unless otherwise indicated, all parts and percentages are based on weight.
[0106] raw material:
[0107] Voranol TM 2120 is a polyether polyol which is a liquid at room temperature and is available from Dow Chemical Company.
[0108] XCP-244 is a polyester polyol which is liquid at room temperature and is available from Xuchuan Chemical Company.
[0109] Priplast 3172 is a solid polyester polyol having a melting point of 40°C, available from Croda.
[0110] Dynacoll 7360 is a solid polyester polyol having a melting point of 55°C, available from Evonik Industries AG.
[0111] Dynacoll 7380 is a solid polyester polyol having a melting point of 70°C, available from Evonik Industries AG.
[0112] Capa TM 2302 is a solid polycaprolactone polyol with a melting point of 50°C available from Ingevity.
[0113] DESMODUR 44C FUSED is an MDI available from Covestro.
[0114] Test method:
[0115] Horizontal liquidity test
[0116] Sample preparation:
[0117] A polycarbonate substrate with 20 wt% glass fiber of size 101.6 mm * 25.4 mm * 1 mm was cleaned with isopropyl alcohol and left idle for a few minutes under ambient conditions to ensure that the surface was completely dry. Then, the sample composition was heated to 110°C and maintained for at least 20 minutes, and then the molten sample composition was dispensed onto the substrate through a needle at an air pressure of 3 bar. The width of the original adhesive composition was controlled to about 1 mm, and the gap between the substrate and the needle was about 0.4 to 0.5 mm. After 30 seconds of dispensing, the width of the adhesive bead was measured and recorded as W1; and after 30 minutes, when the composition was fully cured, the width of the cured bond was recorded as W2.
[0118] The horizontal liquidity ratio is calculated based on the following formula:
[0119] Horizontal liquidity ratio = (W2-W1) / W1*100%
[0120] In case the horizontal flow ratio is greater than or equal to 10%, preferably greater than 15%, more preferably greater than 25%, the horizontal flow of the adhesive composition is considered to be acceptable.
[0121] Vertical flow test
[0122] Sample preparation:
[0123] A transparent polycarbonate (PC) substrate with a size of 101.6mm*25.4mm*1mm was bonded to a stainless steel (SUS) substrate with a size of 101.6mm*25.4mm*1mm, and a test sample with a gap of 2mm in width was formed between the PC substrate and the SUS substrate. The test sample was placed in a position such that the gap was perpendicular to the horizontal plane from top to bottom. Then, the adhesive composition was heated to 110°C and kept for at least 20 minutes, and then the molten adhesive composition was distributed on the top of the gap between the PC substrate and the SUS substrate to fill the entire gap. Finally, after 1 hour of distribution, the vertical height of the bond was measured and recorded.
[0124] The vertical flow of the adhesive composition is considered acceptable when the vertical height of the bond is greater than or equal to 0.2 mm, preferably greater than or equal to 0.5 mm.
[0125] Cross tensile strength test
[0126] Sample preparation:
[0127] i. First, a polycarbonate substrate with 20 wt% glass fiber was prepared, the size of the substrate was 101.6*25.4*1 mm. The substrate was cleaned with isopropyl alcohol and left idle for a few minutes under ambient conditions to ensure that the surface was completely dry. The first substrate and the second substrate were placed crosswise, and the overlapping area would form an adhesive layer sandwiched between them.
[0128] ii. Then, two spacers with a diameter of 0.127 mm were set to control the thickness of the adhesive layer. Before dispensing the adhesive composition, the spacers were placed at the edge of the first substrate, with a distance of 3 mm from the edge of the overlap area.
[0129] iii. Afterwards, the adhesive composition was heated to 110°C in a Loctite 400D dispenser for 30 minutes. A 21# size needle was used to dispense the adhesive composition to the surface of the ink glass. During the dispensing process, two bonding lines were formed by the adhesive beads dispensed through the needle. The two bonding lines were applied in parallel, and each bonding line had a distance of 1.5 to 1.8 mm from the edge of the overlapping area of the two substrates. In addition, the distance between each adhesive bead was controlled at 8 mm, and the distance from the adhesive bead to the edge of the overlapping area of the two substrates was also 8 mm.
[0130] iv. After dispensing, the polycarbonate substrate with 20 wt% of glass fiber was pressed onto it to form a sandwich structure of the overlapped area while leaving two free ends of each substrate. A laminate was then prepared.
[0131] v. A 2 kg weight was applied to the sandwich structure in the overlapped area for 15 seconds. The weight was then removed and the resulting sample was placed at 23° C. and 50% relative humidity for 24 hours to cure the adhesive composition.
[0132] Sample test:
[0133] In order to determine the tensile strength at break of the adhesive layer, the cross tensile strength of the sample is measured by an INSTRON tensile tester at a test speed of 2 mm / min. The load at failure is therefore recorded. When the cross tensile strength is greater than or equal to 0.5 MPa, preferably greater than or equal to 1.0 MPa, the adhesive composition is considered to be acceptable.
[0134] Examples 1 to 7 (Ex. 1 to Ex. 7) and Comparative Examples 1 to 2 (CEx. 1 to CEx. 2)
[0135] Using the components in the amounts (parts by weight) listed in Table 1, an adhesive was prepared by the following method, and the properties were tested using the above-mentioned methods, and the results of the evaluation are shown in Table 1.
[0136] The method for preparing a moisture-curable polyurethane hot melt adhesive composition comprises the following steps:
[0137] i. mixing the polyol at a temperature of 110 to 160 ° C, and then evacuating;
[0138] ii. lowering the reaction temperature and adding the polyisocyanate at a temperature of 80 to 120°C, and then controlling the temperature at 90 to 130°C; and
[0139] iii. Discharge the mixture at a temperature of 90 to 150°C under nitrogen protection.
[0140] Table 1:
[0141]
[0142] As can be seen from Table 1, the moisture-curable polyurethane hot melt adhesive compositions in Examples Ex. 1 to Ex. 3 of the present invention exhibit good horizontal and vertical flow properties and maintain satisfactory tensile strength when cured. However, in the case where the amount of component (c) is greater than 12 wt%, the composition does not substantially have any flowability to meet the application requirements.
[0143] Table 2
[0144]
[0145] As can be seen from Table 2, two moisture-curable polyurethane hot melt adhesive compositions with the same amount of component (c) were prepared, one without any liquid polyol (CEx.2) and the other containing a liquid polyol (Ex.1). The results show that, in the absence of the component (a), the composition adhesive lacks the required fluidity.
[0146] Table 3
[0147]
[0148] As can be seen from Table 3, the moisture-curable polyurethane hot melt adhesive composition of the present invention having the polycaprolactone polyol exhibits improved horizontal flow and higher tensile strength when cured.
[0149] Table 4
[0150]
[0151] As can be seen from Table 4, the use of a liquid polyether polyol in the adhesive composition of the present invention increases the bond strength of the adhesive composition when cured, compared to a liquid polyester polyol.
[0152] Although some preferred embodiments have been described, many modifications and variations are possible in light of the above teachings. It is therefore to be understood that the invention may be practiced other than as specifically described without departing from the scope of the appended claims.
Claims
1. A moisture-curable polyurethane hot melt adhesive composition comprising at least one polyurethane prepolymer obtained by reacting a component comprising (A) a polyol mixture with (B) at least one polyisocyanate having at least two isocyanate groups in one molecule. The polyol mixture comprises: (a) at least one polyol which is liquid at room temperature, (b) at least one crystalline polyester polyol having a melting point below 70°C, and (c) 0 to less than 15.4 wt% of at least one crystalline polyester polyol having a melting point of not less than 70°C, based on the total amount of the composition.
2. The composition according to claim 1, wherein the component (a) has a number average molecular weight of 400 to 8,000 g / mol, preferably 500 to 5,000 g / mol, more preferably 1,000 to 4,000 g / mol.
3. The composition according to any one of the preceding claims, wherein the component (b) comprises at least one crystalline polycaprolactone polyol having a melting point below 70°C.
4. A composition according to any one of the preceding claims, wherein The component (c) is present in an amount of 0 to less than 12 wt%, more preferably 0 to less than 11 wt%, even more preferably 0 to less than 5 wt%, based on the total amount of the composition.
5. The composition according to any one of the preceding claims, wherein the component (B) is selected from 4,4-diphenylmethane diisocyanate (MDI), hydrogenated MDI (H12MDI), partially hydrogenated MDI (H6MDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), 4,4-diphenyldimethylmethane diisocyanate, dialkylene diphenylmethane diisocyanate, tetraalkylene diphenyl methane diisocyanate, 4,4-dibenzyl diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isomers of toluene diisocyanate (TDI), 1-methyl-2,4-diisocyanatocyclohexane, 1,6-diisocyanato-2,2,4-trimethylhexane, 1,6-diisocyanato-2,4,4-trimethylhexane, 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (IPDI), Tetramethoxybutane-1,4-diisocyanate, naphthalene-1,5-diisocyanate (NDI), butane-1,4-diisocyanate, hexane-1,6-diisocyanate (HDI), dicyclohexylmethane diisocyanate, 2,2,4-trimethylhexane-2,3,3-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, ethylene diisocyanate, methylene triphenyl triisocyanate (MIT), diisocyanatoethyl phthalate, Trimethylhexamethylene diisocyanate, 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, and dimer fatty acid diisocyanate, lysine ester diisocyanate, 4,4-dicyclohexylmethane diisocyanate, 1,3-cyclohexane diisocyanate or 1,4-cyclohexane diisocyanate, and mixtures thereof, the most preferred polyisocyanate is 4,4-diphenylmethane diisocyanate (MDI) and its isomers, chain-extended MDI, and mixtures thereof.
6. The composition according to any one of the preceding claims, wherein the at least one polyurethane prepolymer has an NCO content of 1.3 wt% to 6 wt%.
7. A composition according to any one of the preceding claims, wherein the ratio of component (A) to component (B) is selected so that the molar ratio of NCO to OH is from 1.3 to 4.
0.
8. The composition according to any one of the preceding claims, wherein the composition additionally comprises at least one thermoplastic resin.
9. The composition of claim 8, wherein the thermoplastic resin is selected from the group consisting of polyesters, phenoxy resins, phenolic resins, acrylic polymers, acrylic block copolymers, acrylic polymers with tertiary alkylamide functionality, polysiloxane polymers, polystyrene copolymers, polyvinyl polymers, divinylbenzene copolymers, polyetheramides, polyvinyl acetals, polyvinyl butyrals, polyvinyl acetone alcohols, polyvinyl alcohols, polyvinyl acetates, polyvinyl chlorides, methylene polyvinyl ethers, cellulose acetates, styrene-acrylonitrile copolymers, amorphous polyolefins, thermoplastic urethanes, polyacrylonitrile, ethylene vinyl acetate copolymers, ethylene vinyl acetate terpolymers, functionalized ethylene vinyl acetates, ethylene acrylate copolymers, ethylene acrylate terpolymers, ethylene butadiene copolymers and / or block copolymers, styrene butadiene block copolymers, polycaprolactones, and mixtures thereof.
10. A composition according to any one of the preceding claims, wherein The component (a) is present in an amount of greater than 0 wt% to 60 wt%, preferably 10 wt% to 60 wt%, more preferably 15 wt% to 50 wt%, based on the total weight of the composition.
11. A composition according to any one of the preceding claims, wherein The component (b) is present in an amount of greater than 0 wt% to 80 wt%, preferably 10 wt% to 80 wt%, more preferably 15 wt% to 60 wt%, based on the total weight of the composition.
12. A composition according to any one of the preceding claims, wherein The component (B) is present in an amount of 5 wt % to 50 wt %, preferably 10 wt % to 35 wt %, preferably 10 wt % to 30 wt %, based on the total weight of the composition.
13. A method for preparing a hot melt adhesive composition according to any one of claims 1 to 12, comprising the following steps: (i) mixing the polyol and, if present, the thermoplastic resin at a temperature of 110 to 160° C., and then applying a vacuum; (ii) lowering the reaction temperature and adding a polyisocyanate having at least two isocyanate groups in one molecule at a temperature of 70 to 130° C., and then controlling the temperature at 90 to 130° C.; (iii) adding optional additives and mixing until homogeneous; and (iv) discharging the mixture, preferably discharging the mixture at a temperature of 90 to 150° C. under nitrogen protection.
14. A laminate comprising a first substrate, a second substrate, and an adhesive layer sandwiched therebetween, wherein the first substrate and the second substrate are independently selected from glass, resin, metal and polyolefin, and the adhesive layer is formed by curing the adhesive composition according to any one of claims 1 to 12.
15. An electronic device comprising the laminate according to claim 14, or prepared using the adhesive composition according to any one of claims 1 to 12.
16. Use of the adhesive composition according to any one of claims 1 to 12 or the laminate according to claim 14 in a touch screen, a mobile phone, a liquid crystal display, a polymer panel, a film, a conductive layer, a protective layer or an ink layer.
Citation Information
Patent Citations
Single component moisture curing high strength polyurethane adhesive
CN101418203A